Payback : why we retaliate, redirect aggression, and take revenge - Barash, David P. (Oxford University Press, 2011)
From the child taunted by her playmates to the office worker who feels stifled in his daily routine, people frequently take out their pain and anger on others, even those who had nothing to do with the original stress. The bullied child may kick her puppy, the stifled worker yells at his children: Payback can be directed anywhere, sometimes at inanimate things, animals, or other people. In Payback, the husband-and wife team of evolutionary biologist David Barash and psychiatrist Judith Lipton offer an illuminating look at this phenomenon, showing how it has evolved, why it occurs, and what we.